h y Muhui Zhang. - Zhang, Muhui; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book aims to review the history, achievements, and challenges of trilateral cooperation among China, Japan, and South Korea in a systematic way. It offers numerous perspectives to explain the emergence of trilateral institution-building processes and the fluctuations of trilateral cooperation, and underscores three countries$1 (Brespective policy stances towards the building of the triangle. The evolvement of political and economic ties among China, Japan, and South Korea has vital importance to the peace and prosperity of East Asia. Recent years have witnessed the ups and downs of the trilateral cooperation among the three countries. The development of trilateral institution building emerged as a joint gesture in response to the Asian Financial Crisis in the late 1990s. The three countries jointly established multilayered cooperative mechanisms in a wide range of fields. Nonetheless, trilateral cooperation among the three major powers has been proceeding in hardship in the shadow of longstanding geopolitical complexity and the deepening Sino-US confrontations. This book argues that, despite growing economic and social linkages, political animosities have constantly impeded the trilateral cooperation. Relevant to scholars and advanced students in international relations and political economy, this is a vital read in East Asian studies.s
Conceptualization of China-Japan-Korea Trilateral Cooperation in East Asia -- Theories and Analytical Frameworks: Concepts and Utilities of Trilateralism -- Deepening Webs of Functional Trilateralism and Challenges: A Case of Transboundary Air Pollution Cooperation -- The China-Japan-Korea Free Trade Agreement: Politico-Economic Explanations for the Stalled Negotiations -- Proceeding in Hardship: Uncertainties and Fragility of Trilateral Summit Diplomacy -- Korea$1 (Bs Middle Power Diplomacy and Cooperation Initiatives.s
Keywords: Asia -- Politics and government; Social sciences; International economic relations; International relations; Asian Politics; Society; International Political Economy$1 (B.s; International Relations; Foreign Policy